Stranger rape : rapists, masculinity, and penal governance - Bonnycastle, Kevin Denys, 1956-2011 (University of Toronto Press, 2012)
The book's major achievement is to recognize rapists and rape in their particularity and complexity in the hope that critical thinking about their lives and about their experiences in penal contexts and programs may eventually lead to what one respondent called his 'road to redemption'.